Development of a Safety protocol for Management Thirst in the Immediate Postoperative Period - Leonel Alves do Nascimento; Lígia Fahl Fonseca; Edilaine Giovanini Rosseto; Claudia Benedita dos Santos (SciELO, 2014)
Objective To develop a safety protocol for the management of thirst in the immediate postoperative period. Method Quantitative, methodological, and applied study conducted in April-August 2012. An extensive literature search and expert consultation was carried out to develop the protocol and its operating manual. Theoretical and semantic analyzes were carried out by experts. Results Assessment of level of consciousness, reflexes of protection of the airways (cough and swallowing), and absence of nausea and vomiting were selected as safety criteria. These criteria were grouped and formatted in a graph algorithm, which indicates the need to interrupt the procedure if a security criterion does not reach the expected standard. Conclusion The protocol was elaborated to fill in the gap in the literature of a specific model concerning nursing actions in the safe management of thirst in the immediate postoperative period.